HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU PENCEGAHAN KECACINGAN DENGAN STATUS KECACINGAN SISWA SDN 03 PONTIANAK TIMUR KOTAMADYA PONTIANAK TAHUN 2014 - ., Titi Widya Lestari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Worm infection’s case in Indonesia is still high, prevalencein West Borneo is 26,2%. It caused by soil transmitted helminths (STH).STH infection can lead to malnutrition and bring negative impact onphysical growth and cognitive development. STH infection in children cancause them difficult to learn and processing new information. Worminfection can be prevented with the right way of preventions. Objective:To find out the relation between knowledge, attitude and behavior’s levelabout worm infection’s prevention with worm infection’s status ofElementary School Number 3’s students of East Pontianak District in2014. Methods: This research was analytical research and used crosssectional design to 74 subjects. The research began with stool’sexamination to determined worm infection’s status of the students, theninterview to found out knowledge, attitude and behavior’s level of thestudents about worm infection’s prevention. Results: It found out that 12students were infected by STH and all of them caused by Ascarislumbricoides. Fisher’s test result showed that p value for relation of thevariables; knowledge, attitude and behavior’s level about worm infection’sprevention with worm infection’s status, each were 0,113 (p>0,05), 0,903(p>0,05), and 0,557 (p>0,05). P value more than 0,05 showed that therewere no significant relation between those three variables with worminfection’s status. Conclusions: There are no relation betweenknowledge, attitude an behavior’s level about worm infection’s preventionwith worm infection’s status of Elementary School Number 3’s students ofEast Pontianak District. Keywords: knowledge, attitude, behavior, prevention, worm infection’sstatus Note:1. Medical School, Faculty of Medicine, University of Tanjungpura, Pontianak, West Borneo2. Department of Biology and Pathobiology, Faculty of Medicine, University of Tanjungpura, Pontianak, West Borneo3. Department of Parasitology, Faculty of Medicine, University of Tanjungpura, Pontianak, West Borneo